Combining Usability Testing with In-Depth Interview for Online Credit Hour Website Evaluation - Pristi Sukmasetya; Endah Ratna Arumi; Agus Setiawan (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
The Online Credits Hour (KRS) application is one of the existing systems at the University of Muhammadiyah Magelang where the academic community, including lecturers, students, and education staff, produces a large amount of student academic data. Evaluation is necessary to find out whether the system runs well. This study is an effort to evaluate the system employing a usability test consisting of five indicators, namely learning ability, memory, efficiency, errors, and satisfaction. The five indicators materialized in the form of questionnaires to online KRS users. The survey involved 118 respondents. The method of study includes validity and reliability tests. The validity test employs a correlation test. The reliability test uses a simple linear regression analysis test and the comparison uses the significance value Alpha equals 0.05. The validity test for all five indicators results in value above 0.05. The reliability test of all the answers in the questionnaire has a Cronbach's Alpha value of 0.93, which suggests that the whole has correspondence. The evaluation results show that the KRS Online application has the highest value in the memorability indicator at 3.97, indicating that the KRS Online application is easily accessible with easy procedures to obtain data. The lowest value is on the error indicator at a level of 3, which means that the KRS Online website shows many errors, such as a broken link or poor navigation.